2018
DOI: 10.1149/2.0121806jes
|View full text |Cite
|
Sign up to set email alerts
|

Highly Durable, Cost-Effective, and Multifunctional Carbon-Supported IrRu-Based Catalyst for Automotive Polymer Electrolyte Fuel Cell Anodes

Abstract: The design of highly durable, electroactive, and cost-effective catalysts to replace the currently prevalent Pt-based ones has long been a major milestone for expanding the market penetration of fuel cell electric vehicles (FCEVs). Over the past decades, catalyst degradation in automotive fuel cells under transient conditions (e.g., startup/shutdown and cell reversal) has attracted much attention due to its irreversible consequences for the membrane electrode assembly (MEA). Herein, we evaluate IrRu n /C as al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 21 publications
1
30
1
Order By: Relevance
“…Each ink was mixed with a low equivalent weight (EW) of Nafion ionomer (800 EW, 3 M), deionized water, and dipropylene glycol (Sigma‐Aldrich) in a ball mill for 1 hour. MEAs 2.5 × 2.5 cm 2 in size were prepared using the decal transfer method, 22,23 where the inks were cast to the decal transfer film using a doctor blade and the coated films were dried in an oven at 60°C for 10 hours. Then, the electrodes were transferred to the membranes via hot pressing at 165°C for 4 minutes under 8 MPa 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Each ink was mixed with a low equivalent weight (EW) of Nafion ionomer (800 EW, 3 M), deionized water, and dipropylene glycol (Sigma‐Aldrich) in a ball mill for 1 hour. MEAs 2.5 × 2.5 cm 2 in size were prepared using the decal transfer method, 22,23 where the inks were cast to the decal transfer film using a doctor blade and the coated films were dried in an oven at 60°C for 10 hours. Then, the electrodes were transferred to the membranes via hot pressing at 165°C for 4 minutes under 8 MPa 20 .…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in a recent study, iridium and ruthenium alloy with ratio 1:4 on carbon support have been prepared, which shows 120 times better durability than conventional Pt/C catalysts along with same catalytic performance. 80,81 In another study, carbon supports were modified by magnetron deposition of C in nitrogen atmosphere resulting in stronger, anticorrosive substrate for Pt catalysts. This results in increase in durability of electrode with similar performance.…”
Section: Polymer Electrolyte Membrane Fuel Cellsmentioning
confidence: 99%
“…Therefore, several studies have been done in past to develop alternative materials to address the durability issue. For instance, in a recent study, iridium and ruthenium alloy with ratio 1:4 on carbon support have been prepared, which shows 120 times better durability than conventional Pt/C catalysts along with same catalytic performance 80,81 . In another study, carbon supports were modified by magnetron deposition of C in nitrogen atmosphere resulting in stronger, anticorrosive substrate for Pt catalysts.…”
Section: Low‐temperature Fuel Cellsmentioning
confidence: 99%
“…Durst et al compared the HOR activity of carbon-supported nanoparticles of four noble metals (Pt, Ir, Rh, and Pd), which indicated that the activity of Ir is the second highest next to Pt. Furthermore, various studies reported that Ir-containing alloy nanoparticles (such as Ir–Ru, Ir–Ru–Y, Ir–V, , and Ir–Co ) exhibit HOR activity comparable to that of Pt. Although the extremely low abundance and high cost of Ir must be considered, the use of second (or third) alloying elements could address this problem.…”
Section: Introductionmentioning
confidence: 99%